Macroscopic porous MnO2 aerogels for supercapacitor electrodes. Issue 8 (17th June 2016) - Xu, Kongliang; Zhu, Xuedong; She, Ping; Shang, Yinxing; Sun, Hang; Liu, Zhenning
Abstract : Supercapacitor electrodes fabricated from macroscopic porous MnO2 aerogels have demonstrated enhanced specific capacitance, high rate capability and excellent cycling durability. Abstract : A supercapacitor electrode has been fabricated from macroscopic porous MnO2 aerogels, and has demonstrated an enhanced specific capacitance, a high rate capability and excellent cycling durability. The improvement of supercapacitive performance can be attributed to the macro interconnected channels in the aerogel structure, which can not only facilitate mass transfer and reduce dead volume, but also provide an additional benefit of relieving stress.